Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1136/bmj.i974
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysed formula and risk of allergic or autoimmune disease: systematic review and meta-analysis

Abstract: ObjeCtiveTo determine whether feeding infants with hydrolysed formula reduces their risk of allergic or autoimmune disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
168
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 183 publications
(183 citation statements)
references
References 51 publications
2
168
0
13
Order By: Relevance
“…( [31][32][33][34] Potential alternative data sources for the efficacy of the intervention would have been one of several meta-analyses, (21,(27)(28)(29) However, there is some disagreement between different meta-analyses conducted at different times by different researchers regarding the effect of hydrolysed formula on AD risk. Three such analyses (21,27,28) concluded several years ago that hydrolysed formulas are recommended in the first 4-6 months of life for the primary prevention of allergic diseases in high-risk infants who are unable to be completely breastfed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…( [31][32][33][34] Potential alternative data sources for the efficacy of the intervention would have been one of several meta-analyses, (21,(27)(28)(29) However, there is some disagreement between different meta-analyses conducted at different times by different researchers regarding the effect of hydrolysed formula on AD risk. Three such analyses (21,27,28) concluded several years ago that hydrolysed formulas are recommended in the first 4-6 months of life for the primary prevention of allergic diseases in high-risk infants who are unable to be completely breastfed.…”
Section: Discussionmentioning
confidence: 99%
“…Three such analyses (21,27,28) concluded several years ago that hydrolysed formulas are recommended in the first 4-6 months of life for the primary prevention of allergic diseases in high-risk infants who are unable to be completely breastfed. A more recent meta-analysis by Boyle et al (29) came to a very different conclusion, adopting a more critical assessment of the published literature (notably concerning publication bias, among others). This recent analysis indicated that the current guidelines recommending hydrolysates to prevent allergic disease in high-risk infants are not supported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, the baby food industry claimed that formulas containing hydrolysed proteins reduce the risk of allergies, whilst eminent scientific reviews have found no evidence to support this claim (Boyle et al, 2016). The claims of "hypoallergenic" or "HA" branding is permitted in labelling laws in many countries, despite the evidence for such claims being derived from studies sponsored by the baby food industry, with unsubstantiated results.…”
Section: Tactic 5: Discrediting Proven Sciencementioning
confidence: 99%
“…Industryfunded research is often selective and more favourable to the use of breastmilk substitutes than independently funded research (Boyle et al, 2016). Further, it sponsored conferences and health professional associations (Academy of Nutrition and Dietetics, 2017; Japan Society of Nutrition and Food Science, Science Council of Japan, 2015;International Nutrition Foundation, 2016;Rollins et al, 2016;Allers, 2013;Costello et al, 2017), using such sponsorship to influence and divert policy decisions and portray their products as necessary.…”
Section: Tactic 5: Discrediting Proven Sciencementioning
confidence: 99%